Monkeypox: a re-emergent virus with global health implications – a comprehensive review - Nourhan G. Naga; Enas A. Nawar; A’laa A. Mobarak; Aya G. Faramawy; Hend M. H. Al-Kordy (Tropical Diseases, Travel Medicine and Vaccines)
Abstract Monkeypox virus (MPXV) is an enclosed, double-stranded DNA virus from the Orthopoxvirus genus, which also contains variola, vaccinia, and cowpox. MPXV, which was once confined to West and Central Africa, has recently had a rebound, spreading beyond its original range since 2017. The virus is distinguished by its unique morphology, which includes an oval or brick-shaped structure and a complex lipid and protein makeup. The current multi-country outbreak designated a public health emergency in 2022, has highlighted MPXV’s shifting epidemiology and ability to spread rapidly over the globe. ‘No one is safe until everyone is safe’ is a slogan we often heard during the COVID-19 pandemic, which is now also required for the growing global and regional mpox outbreaks. The epidemic is divided into two clades: Clade I and Clade II, which have distinct pathogenic characteristics. Diagnostic approaches have developed with advances in molecular techniques, yet problems persist in resource-constrained situations. This overview summarizes the virus’s history, epidemiology, morphology, and clinical characteristics, offering insights into its recent comeback and current global response efforts.